Prenatal diagnosis: 10-year experience - Sirivatanapa P. (2014)
To evaluate the indications and results of prenatal diagnosis of the high risk pregnant women attending the antenatal care clinic at Maharaj Nakorn Chiang Mai Hospital, Chiang Mai University during 1988-1998, we analysed 2,315 amniocenteses, 1,000 cordocenteses, and 11,895 obstetric ultrasound examinations. Among the amniocentesis group, 2,017 cases (87%) were done with the indication of advanced maternal age. The prevalence of major abnormal fetal chromosomes among high risk pregnancies was 1:58. Of 1,000 cases with cordocentesis, the most common indication was fetal risk of severe thalassemia (658 cases; 65.8%) and followed by fetal risk of chromosome abnormalities (272 cases; 27.2%). In the group of cordocentesis for diagnosis of thalassemia, 99 and 49 pregnancies were affected with Hb Bart's disease and homozygous beta-thalassemia, respectively. Thirty three cases with indication of chromosome analysis had fetuses with abnormal chromosomes. The major indications of ultrasonography included suspicion of intrauterine growth restriction (IUGR), determination of gestational age and screening anomalies, respectively. In conclusion, our extensive experience has enabled us to prenatally detect most fetuses with severe thalassemia, and fetuses with abnormal chromosomes as well as anomalies in a significant number, contributing a great deal to our population. Therefore, we recommend that systematic prenatal diagnosis, either amniocentesis, cordocentesis or ultrasound should be provided to every high risk pregnant woman for a healthy newborn.